Understanding the Management and Leadership Culture of the Innovative Automotive Companies - OKATAN, KAĞAN (Bandırma Onyedi Eylül Üniversitesi İ.İ.B.F., 2020)
Management and leadership styles and approaches have always been important for business and management literature. The dominance of management and leadership on companies’ success or failure has been highlighted and investigated by important amount of studies in existing literature. This study investigates the management and leadership culture type of sample innovative companies from automotive industry by applying ‘competing values framework assessment’ . This study also identifies the culture types of other dimensions of organizational culture and provides a consolidated view. The results demonstrated the dominance of market culture which fosters competition among the members of the organization and success oriented. On the other hand, hierarchy culture has considerable existence in the ‘management of employees’ dimension of the organizational culture. All four culture types’ existence levels are also represented in the study for all dimensions of organizational culture.

İşletme ve yönetim literatürü için yönetim ve liderlik stilleri ve yaklaşımları her zaman önemli olmuştur. Şirketlerin başarısı veya başarısızlığı üzerindeki yönetim ve liderliğin baskınlığı, mevcut literatürdeki önemli çalışmalarla vurgulanmış ve araştırılmıştır. Bu çalışma, otomotiv endüstrisinden yenilikçi görülen örnek firmaların yönetim ve liderlik kültürü türlerini “rekabetçi değerler çerçeve değerlendirmesi” uygulayarak incelemektedir. Bu çalışma, örgütsel kültürün diğer boyutlarının kültür türlerini de tanımlamakta ve konsolide bir görüş sunmaktadır. Sonuçlar, organizasyon üyeleri arasındaki rekabeti teşvik eden ve başarı odaklı pazar kültürünün baskınlığını göstermiştir. Öte yandan,hiyerarşi kültürü, örgüt kültürünün 'çalışanların yönetimi' boyutunda önemli bir varlığa sahiptir. Çalışmada, dört kültür türünün varoluş düzeyi de örgütsel kültürün tüm boyutları için gösterilmektedir.
Yenilikçi Otomotiv Şirketlerinin Yönetim Ve Liderlik Kültürünü Anlamak
Keywords: Business Administration; Management of Technological Innovation and R&d; Personnel Management; Corporate Culture